Level Of Planning For The Program To Improve Chili Cultivation In Sapanang Village, Binamu District, Jeneponto Regency - Asriadi, Andi Amran; Nailah Husain; Sahlan; Siti Wardah (Cita konsultindo, 2025)
The purpose of this study was to analyze the extent of farmer participation in planning chili development extension programs in Sanapang Village, located in Binamu Subdistrict, Jeneponto Regency. The study was conducted using a survey method. The research sample was taken purposively in Sanapang Village. All farmers who were members of farmer groups were included in the research population. The selection of farmer samples was carried out using a simple random method using the Slovin formula, resulting in 250 farmers as samples, 25 of whom represented 10%. For data analysis, this study used quantitative descriptive analysis and calculated the mean and percentage using the Likert scale approach. The research findings revealed that the implementation of the agricultural extension program showed the following results: the participation of member farmers in extension activities in response to planning reached 2.49%, which indicates a less active category, while the response to the preparation of the agricultural extension program scored 2.41%, which also falls into the less active category. There are several factors that influence the low participation in the planning of the agricultural extension program. Among these factors are the lack of farmer involvement in the planning process, inadequate extension infrastructure, and the mismatch between the plan and farmers' needs. In addition, geographical conditions and economic factors also make it difficult for farmers to access existing programs. Internal factors related to extension workers, such as skills and experience, as well as a lack of coordination with various local parties